Public services and agglomeration effect under spatial structure: Threshold verification on the provincial capital cities in China - Mei-Qi Li; Ziyan Li; Wei Zhang; Zehao Wang; Yong Zhang (PLoS ONE, 2025)
This paper explains the relationship between public services expenditure and agglomeration economy from the perspective of spatial structure, considering that the allocation of public service expenditure by local governments does not fully leverage the benefits of agglomeration effects. We constructed a general equilibrium model that examines the close relationship between public service expenditure and agglomeration effect. From a spatial structure perspective, regions are categorized into monocentric and polycentric spatial structures. We discussed the scale of urban expansion and the level of public service expenditure in secondary cities across these different types of spatial structures. It was examined 31 provincial capitals of China as research samples to validate the applicability of theoretical mechanism analysis. Six models were constructed using 2S-GMM to investigate the relationship between the public service expenditure and agglomeration effect. Meanwhile, the PTR method was employed to develop 36 models to assess the threshold effect of urban expansion scale and public service expenditure in the second city of the region, focusing on the influence mechanism of public service expenditure allocation on the agglomeration effect. Three noteworthy conclusions are as follows: (1) the scale and structure of public service expenditure has a positive influence on agglomeration effect. (2) in monocentric structure areas, we should focus on the impact of the public services expenditure structure on agglomeration effect in the changes of urban scale. (3) in polycentric structure areas, we should focus on the impact of the public services expenditure structure on agglomeration effect in the changes of scale of public services in the second central city. This research not only have enhanced the theoretical influence mechanism of public service expenditure on the agglomeration effect from the perspective of spatial structure, but also offers guidance on the allocation of public service expenditure in provincial capital cities.